Anticipated and experienced pain associated with root canal treatment in a teaching dental hospital in India: A survey - Natasha Gupta; Neelam Singh (Wolters Kluwer Medknow Publications, 2023)
Introduction: The pain associated with endodontic therapy brings about a lot of fear and anxiety. This fear sometimes leads to patient avoiding to get the appropriate treatment and save the tooth. It becomes very important that the patient is well guided so he can resort to save the tooth rather than extract it. This study was undertaken to evaluate the pain which is felt before getting the treatment (anticipated pain) and also pain which was actually experienced (experienced pain). Methodology: This pilot study was conducted on a population of 100 in government dental colleges and hospitals. The consent was taken, and two questionnaires were got filled pretreatment and posttreatment. These questionnaires used a Modified Visual Analog Scale (0-3, 0 = no pain, 1 = mild, 2 = moderate, and 3 = severe). Results: The data were analyzed using the Chi-square test and Kruskal-Wallis test. To statistically compare anticipated and experienced pain scores, the Wilcoxon test was used. Conclusions: This study showed that the anticipated pain was more than experienced pain. The two major reasons for the patients to withdraw from getting the treatment are the cost factor and the pain associated while getting the treatment done. Good anesthesia techniques help reduce the pain experienced and hence reduce the overall anxiety of the patient.